The digital game at the time of covid: strategy to support distance learning - Lizzi, Federica (Opción, 2022)
The covid19 pandemic determined a dramatic change on a global scale also in the educational and didactic scope: suddenly, we went from teaching and learning in person to online classes. Such situation greatly affected the didactic methods: teachers were forced to adopt new strategies in order to communicate, interact and raise the students’ motivation and involvement. They had to reinvent themselves and change their teaching methods, stimulating students’ creativity so they could improve their learning results. This article aims to highlight the reasons behind many teachers’ choice to pursue learning through digital games.